Green and healthy phase change energy storage material and production method thereof
By using Eloshi nanotube microcapsule structure and specific proportion raw materials in phase change energy storage materials, the problems of low thermal conductivity and easy leakage of existing phase change energy storage materials are solved, and the high thermal conductivity and fire resistance are improved, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202510082886.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
Existing phase change energy storage materials have problems such as low thermal conductivity, easy leakage, slow thermal conductivity, and possible release of harmful chemicals during production and use, which affects their application in energy utilization and environmental protection.
Develop a green and healthy phase change energy storage material, and combines 3-aminopropyltriethoxysilane modification and titanate coupling agent to modify the ratio of copper nanoparticles, nano aluminum hydroxide, nanoborate and compatibility agents to form a material with high thermal conductivity and good fire resistance.
It significantly improves the thermal conductivity and fire resistance of the material, extends the service life, reduces the risk of leakage, enhances the stability and reliability of the material, and is suitable for a variety of application scenarios.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite functional materials, and in particular to a green and healthy phase change energy storage material and a production method thereof. Background Art
[0002] At a time when energy utilization and environmental protection are increasingly valued, phase change energy storage materials are becoming more and more important in many fields. However, existing phase change energy storage materials have many defects. From the perspective of heat transfer performance, many materials have low thermal conductivity and slow heat transfer, which greatly affects the efficiency of energy storage and release, resulting in the inability to timely and effectively utilize or release energy. Although liquid paraffin is a commonly used phase change material, it has the risk of leakage, low thermal conductivity, and slow heat absorption and release process, which limits the continuous operation of the equipment, and precipitation will occur during use. In addition, some traditional phase change energy storage materials will release harmful chemicals during production, use or disposal, posing a potential threat to human health and the ecological environment, which is not in line with the development trend of green environmental protection and health and safety. Therefore, it is urgent to develop new phase change energy storage materials to overcome these problems. Summary of the invention
[0003] In order to solve at least one of the above technical problems and develop an environmentally friendly, safe, stable and thermally conductive composite functional material, the present application provides a green and healthy phase change energy storage material and a production method thereof.
[0004] In a first aspect, the present application provides a green and healthy phase change energy storage material. The phase change energy storage material is a halloysite nanotube microcapsule by weight; the halloysite nanotube microcapsule comprises the following raw materials by weight:
[0005] 10-30 parts of halloysite nanotubes, 0.5-3 parts of 3-aminopropyltriethoxysilane, 50-90 parts of liquid paraffin, 5-9 parts of titanate coupling agent modified copper nanoparticles, 5-20 parts of nano aluminum hydroxide, 2.5-10 parts of nano borate, and 5-15 parts of a compatibilizer;
[0006] The halloysite nanotube microcapsules further include sodium dodecyl sulfate, methyl methacrylate and an initiator;
[0007] The amount of sodium dodecyl sulfate added is 1%-5% of the weight of the halloysite nanotubes;
[0008] The amount of methyl methacrylate added is 5%-15% by weight of the halloysite nanotubes;
[0009] The added amount of the initiator is 0.5%-1.5% of the weight of methyl methacrylate.
[0010] By adopting the above technical scheme, the present application effectively solves many problems of existing phase change energy storage materials through a carefully designed raw material formula and ratio. After the halloysite nanotubes are modified by 3-aminopropyltriethoxysilane, they can form a good support and heat transfer structure, greatly improve the thermal conductivity of the material, accelerate the heat transfer speed, improve the energy storage and energy release efficiency, and solve the problem of poor heat transfer performance; the compound use of liquid paraffin and titanate coupling agent modified copper nanoparticles provides a better thermal conductivity for the material, and there is a strong interaction between the titanate coupling agent modified copper nanoparticles and the liquid paraffin molecules, which can effectively prevent the aggregation and sedimentation of liquid paraffin molecules. The microcapsules in this application are added with nano aluminum hydroxide and nano borate, which further enhances the fire resistance of the material and reduces the risk of fire. At the same time, the density of the material is improved to a certain extent, making the overall structure of the material more compact and stable, and optimizing the comprehensive performance. However, since nano aluminum hydroxide and nano borate have a large specific surface area, precipitation and aggregation phenomena are very likely to occur in the material system, and it is difficult to achieve uniform dispersion in the halloysite nanotubes, which seriously interferes with the comprehensive performance of the material. To this end, the present application cleverly introduces a compatibilizer to improve the compatibility between the components and avoid the interface incompatibility phenomenon when combined with the matrix material. Moreover, the microcapsule structure in the present application is like a precision protective shell, which tightly wraps the core part of the phase change material to form a relatively independent and stable space, greatly reducing the direct contact between the phase change material and the external environment, effectively avoiding the volatilization and leakage of the phase change material, and significantly extending the service life of the material; at the same time, the microcapsule structure gives the material good flexibility and plasticity, so that it can easily adapt to various complex shapes and different sizes of application requirements, greatly broadening the application range of the material; in addition, the microcapsule structure also plays a good buffering role in the phase change process, making the energy storage and release process more stable and controllable, further optimizing the phase change performance of the material, ensuring that the material can operate stably and efficiently under various working conditions, and fully demonstrating the significant advantages of the phase change energy storage material of this application in performance improvement and application expansion.
[0011] In some embodiments, the weight ratio of the liquid paraffin to the titanate coupling agent modified copper nanoparticles is 1:(0.08-0.15).
[0012] By adopting the above technical solution, the liquid paraffin and titanate coupling agent modified copper nanoparticles in this ratio can fully utilize the high thermal conductivity advantage of the titanate coupling agent modified copper nanoparticles on the basis of ensuring that the material has good phase change properties, and significantly improve the overall thermal conductivity of the material. Because the copper nanoparticles are evenly dispersed in the liquid paraffin at this ratio, the two are closely combined, which greatly speeds up the transfer of heat inside the material, making the material more efficient in the process of energy storage and release, and effectively improving the slow energy conversion problem caused by low thermal conductivity of traditional phase change materials.
[0013] Preferably, the weight ratio of the liquid paraffin and the titanate coupling agent modified copper nanoparticles is 1:0.1.
[0014] By adopting the above technical solutions, the thermal conductivity of the material is further improved, and the heat transfer is faster and more efficient, thereby significantly improving the efficiency of energy storage and release.
[0015] In some embodiments, the diameter of the halloysite nanotubes is 30-60 nm and the length is 0.8-1.5 μm.
[0016] In some embodiments, the compatibilizer includes at least one of calcium lignin sulfonate and polyvinyl pyrrolidone.
[0017] By adopting the above technical scheme, calcium lignin sulfonate and polyvinyl pyrrolidone can significantly improve the compatibility between the various components of the material by virtue of their unique chemical properties. A close connection is established between the material components of different properties, so that nano aluminum hydroxide and nano borate are evenly dispersed in the halloysite nanotube system, effectively avoiding the precipitation and aggregation caused by the large specific surface area, and ensuring the uniformity of the internal structure of the material. In the preparation and use of the material, the surface tension difference between the components can be reduced, the interface incompatibility can be reduced, and the occurrence of stratification and shedding problems can be prevented, which effectively guarantees the integrity and reliability of the material and improves the overall performance of the material. At the same time, both calcium lignin sulfonate and polyvinyl pyrrolidone have good chemical stability and environmental protection, and will not adversely affect the environmental health characteristics of phase change energy storage materials. Instead, they further enhance the advantages of the material in practical applications and broaden its application range in fields with high requirements for environmental protection and performance.
[0018] Preferably, the compatibilizer comprises calcium lignin sulfonate and polyvinyl pyrrolidone in a weight ratio of 1:1.
[0019] In some embodiments, the initiator includes azobisisobutyronitrile.
[0020] In a second aspect, the present application provides a method for producing a green and healthy phase change energy storage material, the production method comprising the following steps:
[0021] S1, calcining the halloysite nanotubes and then adding them to a hydrochloric acid solution, stirring and reacting at 60-80° C. for 2-4 hours, separating and washing to obtain acid-treated halloysite nanotubes;
[0022] S2, mixing the acid-treated halloysite nanotubes, ethanol and 3-aminopropyltriethoxysilane in step S1, stirring and reacting at 60-80° C. for 4-6 hours, separating and washing to obtain 3-aminopropyltriethoxysilane-modified halloysite nanotubes;
[0023] S3, mixing liquid paraffin and titanate coupling agent modified copper nanoparticles to prepare a phase change material, which is set aside; mixing a compatibilizer with water to prepare a compatibilizer aqueous solution, which is set aside;
[0024] S4, mixing the 3-aminopropyltriethoxysilane-modified halloysite nanotubes described in step S2, the phase change material described in step S3, the compatibilizer aqueous solution described in step S3, and the nano-aluminum hydroxide and nano-borate with water to prepare an aqueous phase;
[0025] S5. Add sodium dodecyl sulfate to the aqueous phase in step S4 and stir to obtain an emulsion, and add methyl methacrylate and an initiator to the emulsion. Under nitrogen protection, react at 60-80° C. for 2-5 hours, and obtain the halloysite nanotube microcapsules after centrifugation, washing and drying.
[0026] By adopting the above technical scheme, the present application firstly carries out roasting and acid treatment of the halloysite nanotubes in step S1, which can effectively remove the impurities on its surface, improve its surface properties, provide better conditions for subsequent modification reactions, and solve the problem that the impurities on the surface of the halloysite nanotubes affect the material properties. Under the action of acid, some chemical bonds on the surface of the halloysite nanotubes are broken and reorganized, making the surface more rough and porous, greatly increasing its specific surface area. This structural change provides more active sites for subsequent chemical reactions, which is conducive to better combination with other substances. At the same time, acid treatment can also regulate the charge properties on the surface of the halloysite nanotubes, enhance its dispersibility and affinity in the subsequent reaction system, and provide a more ideal basis for subsequent modification reactions, thereby effectively solving the problem that the impurities on the surface of the halloysite nanotubes affect the material properties. In S2, the halloysite nanotubes after acid treatment are modified with 3-aminopropyltriethoxysilane to form a good support and heat transfer structure, which significantly improves the thermal conductivity of the material and solves the problem of poor heat transfer performance. Phase change material and compatibilizer aqueous solution are prepared in S3 respectively, in preparation for subsequent mixing. In S4, a variety of raw materials are mixed to obtain an aqueous phase, so that the components are initially contacted and fused. In step S5, sodium dodecyl sulfate, methyl methacrylate and an initiator are added to react, and halloysite nanotube microcapsules are successfully prepared. The microcapsule structure provided in the present application is compact and effectively wraps the phase change material, which not only improves the stability of the material and reduces the leakage risk of the phase change material, but also significantly improves the thermal conductivity, fire resistance and other comprehensive properties of the material through the joint action of various components, so that the prepared phase change energy storage material meets the requirements of green, healthy, efficient and stable, and can meet the needs of various practical application scenarios.
[0027] In some embodiments, the stirring speed in step S5 is 1000-2000 r / min.
[0028] In some embodiments, the particle size of the halloysite nanotube microcapsules is 1-10 μm.
[0029] In a third aspect, the present application provides an application of the green and healthy phase change energy storage material in the fields of building insulation materials, cold chain transportation packaging, and electronic equipment heat dissipation.
[0030] By adopting the above technical solution, in the field of building insulation materials, the phase change energy storage material provided by this application can efficiently store and release heat when the external temperature fluctuates by virtue of its excellent phase change characteristics. When the indoor temperature rises, the material absorbs and stores heat to prevent indoor overheating; and when the temperature drops, the stored heat can be released to maintain indoor warmth, effectively reducing the energy consumption of heating and cooling in buildings and reducing energy costs. At the same time, its environmentally friendly and healthy characteristics also meet the needs of modern buildings for green materials, providing strong support for creating a comfortable, energy-saving and environmentally friendly living environment.
[0031] In terms of cold chain transportation packaging, the material's stable phase change performance and good thermal insulation effect play a key role. It can maintain a low temperature environment inside the package for a certain period of time, ensuring that items in cold chain transportation, such as medicines and food, are always in a suitable temperature range, effectively extending the freshness and shelf life of the items, and ensuring the quality and safety of cold chain transportation. In addition, the material's microcapsule structure gives it good flexibility and compression resistance, and it can adapt to bumps and collisions during transportation, and is not easily damaged, further improving the reliability of cold chain packaging.
[0032] In the field of electronic equipment heat dissipation, the high thermal conductivity of the material prepared by special processes is fully demonstrated. It can quickly absorb the heat generated during the operation of electronic equipment and quickly conduct the heat away through an efficient heat transfer structure, effectively reducing the operating temperature of the electronic equipment, avoiding problems such as equipment performance degradation and shortened life due to overheating, improving the stability and reliability of electronic equipment, and providing reliable heat dissipation guarantee for the efficient operation of electronic equipment, helping electronic equipment to continue to develop in the direction of high performance and miniaturization.
[0033] In summary, the present invention includes at least one of the following beneficial technical effects:
[0034] 1. This application effectively solves many problems of existing phase change energy storage materials through carefully designed raw material formulas and ratios. After being modified with 3-aminopropyltriethoxysilane, the halloysite nanotubes can form a good support and heat transfer structure, greatly improve the thermal conductivity of the material, accelerate the heat transfer speed, improve the energy storage and energy release efficiency, and solve the problem of poor heat transfer performance; the compound use of liquid paraffin and titanate coupling agent modified copper nanoparticles provides the material with better thermal conductivity, and there is a strong interaction between the titanate coupling agent modified copper nanoparticles and the liquid paraffin molecules, which can effectively prevent the aggregation and sedimentation of liquid paraffin molecules. The microcapsules in this application are added with nano aluminum hydroxide and nano borate, which further enhances the fire resistance of the material and reduces the risk of fire. At the same time, the density of the material is improved to a certain extent, making the overall structure of the material more compact and stable, and optimizing the comprehensive performance. However, since nano aluminum hydroxide and nano borate have a large specific surface area, precipitation and aggregation phenomena are very likely to occur in the material system, and it is difficult to achieve uniform dispersion in the halloysite nanotubes, which seriously interferes with the comprehensive performance of the material. To this end, the present application cleverly introduces a compatibilizer to improve the compatibility between the components, avoids the interface incompatibility phenomenon when combined with the matrix material, and prevents stratification. Moreover, the microcapsule structure in the present application is like a precision protective shell, which tightly wraps the core part of the phase change material to form a relatively independent and stable space, greatly reducing the direct contact between the phase change material and the external environment, effectively avoiding the volatilization and leakage of the phase change material, and significantly extending the service life of the material; at the same time, the microcapsule structure gives the material good flexibility and plasticity, so that it can easily adapt to various complex shapes and different sizes of application requirements, greatly broadening the application range of the material; in addition, the microcapsule structure also plays a good buffering role in the phase change process, making the energy storage and release process more stable and controllable, further optimizing the phase change performance of the material, ensuring that the material can operate stably and efficiently under various working conditions, and fully demonstrating the significant advantages of the phase change energy storage material of the present application in performance improvement and application expansion.
[0035] 2. The microcapsule structure provided in this application is tight and effectively wraps the phase change material, which not only improves the stability of the material and reduces the leakage risk of the phase change material, but also through the joint action of various components, significantly improves the thermal conductivity, fire resistance and other comprehensive properties of the material, so that the prepared phase change energy storage material meets the requirements of green, healthy, efficient and stable, and can meet the needs of various practical application scenarios. DETAILED DESCRIPTION
[0036] The present application is further described in detail below with reference to the embodiments.
[0037] Unless otherwise specified, the raw materials used in this application are commercially available.
[0038] At a time when energy utilization and environmental protection are increasingly valued, phase change energy storage materials are becoming more and more important in many fields. However, existing phase change energy storage materials have many defects. From the perspective of heat transfer performance, many materials have low thermal conductivity and slow heat transfer, which greatly affects the efficiency of energy storage and release, resulting in the inability to timely and effectively utilize or release energy. Although liquid paraffin is a commonly used phase change material, it has the risk of leakage, low thermal conductivity, and slow heat absorption and release process, which limits the continuous operation of the equipment, and precipitation will occur during use. In addition, some traditional phase change energy storage materials will release harmful chemicals during production, use or disposal, posing a potential threat to human health and the ecological environment, which is not in line with the development trend of green environmental protection and health and safety. Therefore, it is urgent to develop new phase change energy storage materials to overcome these problems.
[0039] Therefore, in order to solve at least one of the above technical problems, the inventors of the present application have developed a composite functional material that is environmentally friendly, safe, has good stability and high thermal conductivity. In the first aspect, a green and healthy phase change energy storage material is provided. The phase change energy storage material is halloysite nanotube microcapsules by weight; the halloysite nanotube microcapsules include the following raw materials by weight:
[0040] 10-30 parts of halloysite nanotubes, 0.5-3 parts of 3-aminopropyltriethoxysilane, 50-90 parts of liquid paraffin, 5-9 parts of titanate coupling agent modified copper nanoparticles, 5-20 parts of nano aluminum hydroxide, 2.5-10 parts of nano borate, and 5-15 parts of a compatibilizer;
[0041] The sodium dodecyl sulfate-halloysite nanotube microcapsules further include sodium dodecyl sulfate, methyl methacrylate and an initiator;
[0042] The amount of sodium dodecyl sulfate added is 1%-5% of the weight of the halloysite nanotubes;
[0043] The amount of methyl methacrylate added is 5%-15% by weight of the halloysite nanotubes;
[0044] The amount of initiator added is 0.5%-1.5% of the weight of methyl methacrylate. This application is based on this scheme. This application effectively solves many problems of existing phase change energy storage materials through carefully designed raw material formulas and ratios. After being modified with 3-aminopropyltriethoxysilane, the halloysite nanotubes can form a good support and heat transfer structure, greatly improve the thermal conductivity of the material, accelerate the heat transfer rate, improve the energy storage and release efficiency, and solve the problem of poor heat transfer performance; the compound use of liquid paraffin and titanate coupling agent modified copper nanoparticles provides the material with better thermal conductivity, and there is a strong interaction between the titanate coupling agent modified copper nanoparticles and the liquid paraffin molecules, which can effectively prevent the aggregation and sedimentation of liquid paraffin molecules. The microcapsules in this application are added with nano aluminum hydroxide and nano borate, which further enhances the fire resistance of the material and reduces the risk of fire. At the same time, the density of the material is improved to a certain extent, making the overall structure of the material tighter and more stable, and optimizing the comprehensive performance. However, due to the large specific surface area of nano-aluminum hydroxide and nano-borates, precipitation and aggregation are very likely to occur in the material system, and it is difficult to achieve uniform dispersion in the halloysite nanotubes, which seriously interferes with the comprehensive performance of the material. To this end, the present application cleverly introduces a compatibilizer to improve the compatibility between the components, avoid interface incompatibility when combining with the matrix material, and prevent stratification and shedding. Moreover, the microcapsule structure in the present application is like a precision protective shell, which tightly wraps the core part of the phase change material to form a relatively independent and stable space, greatly reducing the direct contact between the phase change material and the external environment, effectively avoiding the volatilization and leakage of the phase change material, and significantly extending the service life of the material; at the same time, the microcapsule structure gives the material good flexibility and plasticity, so that it can easily adapt to various complex shapes and different sizes of application requirements, greatly broadening the application range of the material; in addition, the microcapsule structure also plays a good buffering role in the phase change process, making the energy storage and release process more stable and controllable, further optimizing the phase change performance of the material, ensuring that the material can operate stably and efficiently under various working conditions, and fully demonstrating the significant advantages of the phase change energy storage material of this application in performance improvement and application expansion.
[0045] In a second aspect, the present application provides a method for producing a green and healthy phase change energy storage material, the production method comprising the following steps:
[0046] S1, calcining the halloysite nanotubes and then adding them to a hydrochloric acid solution, stirring and reacting at 60-80° C. for 2-4 hours, separating and washing to obtain acid-treated halloysite nanotubes;
[0047] S2, mixing the acid-treated halloysite nanotubes, ethanol and 3-aminopropyltriethoxysilane in step S1, stirring and reacting at 60-80° C. for 4-6 hours, separating and washing to obtain 3-aminopropyltriethoxysilane-modified halloysite nanotubes;
[0048] S3, mixing liquid paraffin and titanate coupling agent modified copper nanoparticles to prepare a phase change material, which is set aside; mixing a compatibilizer with water to prepare a compatibilizer aqueous solution, which is set aside;
[0049] S4, mixing the 3-aminopropyltriethoxysilane-modified halloysite nanotubes described in step S2, the phase change material described in step S3, the compatibilizer aqueous solution described in step S3, and the nano-aluminum hydroxide and nano-borate with water to prepare an aqueous phase;
[0050] S5. Add sodium dodecyl sulfate to the aqueous phase in step S4 and stir to obtain an emulsion, and add methyl methacrylate and an initiator to the emulsion. Under nitrogen protection, react at 60-80° C. for 2-5 hours, and obtain the halloysite nanotube microcapsules after centrifugation, washing and drying.
[0051] This application is based on this solution. The microcapsule structure provided by this application is tight and effectively wraps the phase change material, which not only improves the stability of the material and reduces the leakage risk of the phase change material, but also through the joint action of various components, significantly improves the thermal conductivity, fire resistance and other comprehensive properties of the material, so that the prepared phase change energy storage material meets the requirements of green, healthy, efficient and stable, and can meet the needs of various practical application scenarios.
[0052] On the third aspect, the present application provides an application of the green and healthy phase change energy storage material in the fields of building insulation materials, cold chain transportation packaging, and electronic equipment heat dissipation. The present application is based on this scheme. In the field of building insulation materials, the phase change energy storage material provided by the present application can efficiently store and release heat when the external temperature fluctuates by virtue of its excellent phase change characteristics. When the indoor temperature rises, the material absorbs and stores heat to avoid indoor overheating; when the temperature drops, the stored heat can be released to maintain indoor warmth, effectively reducing the energy consumption of heating and cooling in buildings, and reducing energy costs. At the same time, its environmentally friendly and healthy characteristics also meet the needs of modern buildings for green materials, and provide strong support for creating a comfortable, energy-saving and environmentally friendly living environment.
[0053] In terms of cold chain transportation packaging, the material's stable phase change performance and good thermal insulation effect play a key role. It can maintain a low temperature environment inside the package for a certain period of time, ensuring that items in cold chain transportation, such as medicines and food, are always in a suitable temperature range, effectively extending the freshness and shelf life of the items, and ensuring the quality and safety of cold chain transportation. In addition, the material's microcapsule structure gives it good flexibility and compression resistance, and it can adapt to bumps and collisions during transportation, and is not easily damaged, further improving the reliability of cold chain packaging.
[0054] In the field of electronic equipment heat dissipation, the high thermal conductivity of the material prepared by special processes is fully demonstrated. It can quickly absorb the heat generated during the operation of electronic equipment and quickly conduct the heat away through an efficient heat transfer structure, effectively reducing the operating temperature of the electronic equipment, avoiding problems such as equipment performance degradation and shortened life due to overheating, improving the stability and reliability of electronic equipment, and providing reliable heat dissipation guarantee for the efficient operation of electronic equipment, helping electronic equipment to continue to develop in the direction of high performance and miniaturization.
[0055] Example 1
[0056] This embodiment provides a green and healthy phase change energy storage material, which includes the following raw materials in parts by weight: 10 parts of halloysite nanotubes, 0.5 parts of 3-aminopropyltriethoxysilane, 70 parts of liquid paraffin, 7 parts of titanate coupling agent modified copper nanoparticles, 5 parts of nano aluminum hydroxide, 2.5 parts of nano borate, and 5 parts of compatibilizer;
[0057] The halloysite nanotube microcapsules further include: sodium dodecyl sulfate, methyl methacrylate and an initiator;
[0058] The amount of sodium dodecyl sulfate added is 1% of the weight of the halloysite nanotubes
[0059] The amount of methyl methacrylate added is 5% by weight of the halloysite nanotubes
[0060] The added amount of the initiator is 0.5% by weight of methyl methacrylate.
[0061] The diameter of the halloysite nanotubes in this embodiment is 30-60 nm and the length is 0.8-1.5 μm.
[0062] The compatibilizer in this embodiment is calcium lignin sulfonate.
[0063] The nano borate in this embodiment is nano zinc borate, and the particle size of nano zinc borate is 100-120 nm.
[0064] The particle size of the nano aluminum hydroxide in this embodiment is 80-120 nm.
[0065] The initiator in this embodiment is azobisisobutyronitrile.
[0066] The production method of the green and healthy phase change energy storage material in this embodiment is as follows:
[0067] S1: After calcining the halloysite nanotubes at 500°C for 2 hours, the nanotubes were added into a 5% hydrochloric acid solution, stirred and reacted at 60°C for 4 hours, and then centrifuged and washed with deionized water to neutrality (pH to neutral) to obtain acid-treated halloysite nanotubes.
[0068] S2: The halloysite nanotubes treated with acid in step S1, 100 parts of ethanol and 0.5 parts of 3-aminopropyltriethoxysilane were mixed, and stirred for reaction at 60° C. for 6 hours. The mixture was centrifuged again, and washed with ethanol for 3 times to obtain 3-aminopropyltriethoxysilane-modified halloysite nanotubes.
[0069] S3: Add nano copper particles (average diameter of 10 nm) to a 5% mass percentage titanate coupling agent ethanol solution (the amount used is 10 times the mass of the nano copper particles) and mix, stir (stirring speed 500 rpm, stirring time 3 hours), centrifuge (centrifugal speed 2000 rpm, centrifugal time 20 minutes), wash (wash 3 times with 20 mL of ethanol each time), and obtain titanate coupling agent modified copper nanoparticles; set aside; mix liquid paraffin and titanate coupling agent modified copper nanoparticles to obtain phase change material, set aside; mix 5 parts of compatibilizer with 50 parts of water to obtain a compatibilizer aqueous solution, set aside. The titanate coupling agent used in this step is isopropyl tri(isostearoyl) titanate.
[0070] S4: Mix the 3-aminopropyltriethoxysilane modified halloysite nanotubes of step S2, the phase change material of step S3, the compatibilizer aqueous solution of step S3, 5 parts of nano aluminum hydroxide, 2.5 parts of nano borate and 30 parts of water to prepare an aqueous phase.
[0071] S5: Add 0.1 parts of sodium dodecyl sulfate to the aqueous phase of step S4 and stir for 30 minutes (stirring speed is 1000r / min) to form a stable water-in-oil emulsion. Add 0.5 parts of methyl methacrylate and 0.0025 parts of initiator to the emulsion, react at 60°C for 5 hours under nitrogen protection, and finally obtain halloysite nanotube microcapsules by centrifugation, washing, and vacuum drying at 60°C for 12 hours.
[0072] Example 2
[0073] The difference between this embodiment and embodiment 1 is that, in this embodiment, when preparing the green and healthy phase change energy storage material, the total weight of liquid paraffin and titanate coupling agent modified copper nanoparticles is 77 parts, wherein the weight ratio of liquid paraffin and titanate coupling agent modified copper nanoparticles is 1:0.08.
[0074] Example 3
[0075] The difference between this embodiment and embodiment 1 is that, in this embodiment, when preparing the green and healthy phase change energy storage material, the total weight of liquid paraffin and titanate coupling agent modified copper nanoparticles is 77 parts, wherein the weight ratio of liquid paraffin and titanate coupling agent modified copper nanoparticles is 1:0.12.
[0076] Example 4
[0077] The difference between this embodiment and embodiment 1 is that, in this embodiment, when preparing the green and healthy phase change energy storage material, the total weight of liquid paraffin and titanate coupling agent modified copper nanoparticles is 77 parts, wherein the weight ratio of liquid paraffin and titanate coupling agent modified copper nanoparticles is 1:0.15.
[0078] Comparative Examples 1-5
[0079] Comparative Example 1
[0080] The difference between this comparative example and Example 1 is that, when preparing the green and healthy phase-change energy storage material, an equal amount of liquid paraffin is used to replace the titanate coupling agent to modify the copper nanoparticles.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 1 is that, when preparing the green and healthy phase-change energy storage material, an equal amount of copper nanoparticles is used to replace the titanate coupling agent to modify the copper nanoparticles.
[0083] Comparative Example 3
[0084] The difference between this comparative example and Example 1 is that, when preparing the green and healthy phase-change energy storage material, the halloysite nanotubes are not modified with 3-aminopropyltriethoxysilane.
[0085] Comparative Example 4
[0086] The difference between this comparative example and Example 1 is that when preparing the green and healthy phase change energy storage material, an equal amount of nano borate is used instead of nano aluminum hydroxide.
[0087] Comparative Example 5
[0088] The difference between this comparative example and Example 1 is that, when preparing the green and healthy phase-change energy storage material, an equal amount of liquid paraffin is used to replace nano borate and nano aluminum hydroxide.
[0089] Experimental testing:
[0090] Latent heat performance test: The sample was heated from room temperature (25°C) to a temperature (k+30°C) 30°C higher than the upper limit of the phase transition temperature of the material (the phase transition temperature k of the material in each embodiment and comparative example was tested first) at a heating rate of 10°C / min under nitrogen protection. After reaching k+30°C, the temperature was then cooled to room temperature (25°C) at a cooling rate of 10°C / min.
[0091] Thermal conductivity test: The sample is processed into a disc with a diameter of 30mm and a thickness of 5mm. The surface flatness error of the disc is required to be within ±0.1mm and the diameter error is within ±0.2mm. The thermal conductivity tester is placed in an environment where the temperature fluctuation does not exceed ±0.5℃ and the relative humidity is 40%-60%. The instrument is calibrated with a standard sample before the test, and the calibration error is within ±2%. Set the temperature at one end to 30℃ and the temperature at the other end to 45℃, measure the heat flow through the sample, and finally calculate the thermal conductivity of the material according to Fourier's law. The unit of thermal conductivity is W / m·K.
[0092] Leakage detection: 50g of phase change energy storage material is placed in a specially made sealed container with a precision balance of 0.001g. The container is placed in a 70°C environment for 72 hours. During this period, the total weight of the container and the internal materials is recorded every 24 hours. If the weight drops significantly (the drop exceeds 0.5% of the initial weight, that is, more than 0.25g), it is determined that the material has leaked.
[0093] Flame retardant performance test (according to GB / T2406.2-2009) is carried out. If the oxygen index is not less than 30%, it is qualified, otherwise it is unqualified.
[0094] The experimental test results of Examples 1-4 and Comparative Examples 1-5 are shown in Table 1.
[0095] Table 1 - Experimental test results of Examples 1-4 and Comparative Examples 1-5
[0096] serial number Latent heat (J / g) Thermal conductivity (W / mK) Is it leaked? Flame retardant Example 1 165 1.32 no qualified Example 2 157 1.25 no qualified Example 3 162 1.28 no qualified Example 4 160 1.26 no qualified Comparative Example 1 145 0.64 no qualified Comparative Example 2 147 1.02 no qualified Comparative Example 3 151 1.11 yes qualified Comparative Example 4 152 1.20 no Failure Comparative Example 5 154 1.28 yes Failure
[0097] Result analysis: The difference between Example 2-4 and Example 1 is that when preparing green and healthy phase change energy storage materials, the total weight of liquid paraffin and titanate coupling agent modified copper nanoparticles remains unchanged, but the weight ratio between the two changes. Combined with the experimental test results in Table 1, it can be seen that when the weight ratio of liquid paraffin and titanate coupling agent modified copper nanoparticles is 1:0.1, the prepared green and healthy phase change energy storage material exhibits higher latent heat and thermal conductivity. The latent heat of Example 1 reaches 165J / g, and the thermal conductivity is 1.32W / (m·K), both higher than Examples 2-4.
[0098] The difference between Comparative Example 1 and Example 1 is that when preparing a green and healthy phase change energy storage material, an equal amount of liquid paraffin is used to replace the titanate coupling agent to modify the copper nanoparticles. Combined with the experimental test data in Table 1, it can be seen that the thermal conductivity of Comparative Example 1 is significantly reduced to 0.64W / (m·K), which is much lower than 1.32W / (m·K) of Example 1. This shows that the modification of copper nanoparticles with titanate coupling agent plays a key role in improving the thermal conductivity of the material, and its absence will seriously weaken the thermal conductivity of the material. However, the latent heat of Comparative Example 1 is 145J / g, which is lower than that of Example 1, but still maintains a certain level, indicating that liquid paraffin, as the main phase change energy storage component, plays a leading role in latent heat performance.
[0099] The difference between Comparative Example 2 and Example 1 is that when preparing a green and healthy phase change energy storage material, an equal amount of copper nanoparticles is used to replace the copper nanoparticles modified by the titanate coupling agent. Combined with the experimental test data in Table 1, it can be seen that the thermal conductivity of Comparative Example 2 is 1.02W / (m·K), which is lower than that of Example 1, indicating that the unmodified copper nanoparticles are not as effective as the copper nanoparticles modified by the titanate coupling agent in improving the thermal conductivity of the material. This may be because the modification process improves the dispersibility of the copper nanoparticles in the material or the interaction with other components, thereby enhancing the thermal conductivity. The latent heat of Comparative Example 2 is 147J / g, which is slightly lower than that of Example 1, and there is no leakage, and the flame retardant performance is qualified, indicating that this replacement has relatively little effect on the latent heat, anti-leakage and flame retardant properties, but has a significant effect on thermal conductivity.
[0100] The difference between Comparative Example 3 and Example 1 is that, when preparing the green and healthy phase change energy storage material, the halloysite nanotubes were not modified with 3-aminopropyltriethoxysilane. Combined with the experimental test data in Table 1, it can be seen that the thermal conductivity of Comparative Example 3 dropped to 1.11W / (m·K), which is lower than that of Example 1, indicating that the modification of the halloysite nanotubes with 3-aminopropyltriethoxysilane is of great significance to the improvement of the thermal conductivity of the material. It may be that the modification process optimizes the structure of the halloysite nanotubes or enhances its combination with other components, thereby promoting heat conduction. In addition, leakage occurred in Comparative Example 3, while there was no leakage in Example 1, indicating that the modification of the halloysite nanotubes is crucial to maintaining the stability of the material structure and preventing leakage. However, the flame retardant properties of Comparative Example 3 are still qualified, indicating that the influence of the modification of the halloysite nanotubes on the flame retardant properties did not cause it to be unqualified under the conditions of this experiment.
[0101] The difference between Comparative Example 4 and Example 1 is that when preparing the green and healthy phase change energy storage material, an equal amount of nano borate is used instead of nano aluminum hydroxide. Comparative Example 4 has unqualified flame retardant performance, which is in sharp contrast to Example 1. This shows that nano aluminum hydroxide plays an indispensable role in maintaining the structural stability of the material in terms of flame retardant performance. After being replaced by nano borate, the performance balance of the material in this regard is destroyed.
[0102] Comparative Example 5 leaked, while Example 1 did not. The reason may be that when they were replaced with liquid paraffin, the stable structure of the material was destroyed, causing the liquid paraffin to escape more easily, resulting in leakage. The flame retardancy of Comparative Example 5 was unqualified because nano-borates and nano-aluminum hydroxide are important flame retardant components. They play a role in the material through a variety of flame retardant mechanisms. After replacing these two components with liquid paraffin, the material lost the key flame retardant guarantee, making the oxygen index lower than 30%, and failed to meet the qualified standard for flame retardant performance.
[0103] In summary, through the analysis of each embodiment and comparative example, it can be seen that the ratio of liquid paraffin and titanate coupling agent modified copper nanoparticles, the modification of copper nanoparticles, the modification of halloysite nanotubes, and the use of nano aluminum hydroxide and nano borate all have an important influence on the performance of green and healthy phase change energy storage materials. The formula and preparation method of Example 1 perform best in comprehensive performance, providing an important reference for further optimization of the material.
[0104] Embodiment 5-6
[0105] The difference between Example 5-6 and Example 1 is that, when preparing the green and healthy phase change energy storage material, the weight proportions of some components are different. The difference is shown in Table 2.
[0106] Table 2 - Differences between Examples 5-6 and Example 1
[0107]
[0108]
[0109] The experimental test results of Examples 5-6 are shown in Table 3.
[0110] Table 3 - Experimental test results of Examples 5-6
[0111] serial number Latent heat (J / g) Thermal conductivity (W / mK) Is it leaked? Flame retardant Example 1 165 1.32 no qualified Example 5 170 1.40 no qualified Example 6 168 1.38 no qualified
[0112] Result analysis: The difference between Examples 5-6 and Example 1 is that when preparing the green and healthy phase change energy storage material, the weight proportions of some components are different. Combined with the experimental test results in Table 3, it can be seen that the comprehensive performance of the green and healthy phase change energy storage material prepared by Example 5 is better.
[0113] Example 7
[0114] The difference between Examples 7-11 and Example 5 is that when preparing green and healthy phase change energy storage materials, the weight ratio of liquid paraffin and titanate coupling agent modified copper nanoparticles is 1:0.1, and the total weight of liquid paraffin and titanate coupling agent modified copper nanoparticles in the green and healthy phase change energy storage material is changed, and the optimal weight ratio is selected.
[0115] In Example 5, the total weight of liquid paraffin and titanate coupling agent modified copper nanoparticles is 77 parts, and the total weight of green and healthy phase change energy storage material is 139.12 parts.
[0116] Therefore, it is not difficult to conclude that in Example 5, the proportion of liquid paraffin (called variable 1) and titanate coupling agent modified copper nanoparticles (called variable 2) in the green and healthy phase change energy storage material (called matrix) is 55.35%.
[0117] The differences between Examples 7-11 and Example 1 are shown in Table 4.
[0118] Proportion = (variable 1 + variable 2) / total weight of matrix 100%.
[0119] Table 4 - Differences between Examples 7-11 and Example 5
[0120]
[0121] The experimental test results of Examples 7-11 are shown in Table 5.
[0122] Table 5 - Experimental test results of Examples 7-11
[0123] serial number Latent heat (J / g) Thermal conductivity (W / mK) Is it leaked? Flame retardant Example 5 170 1.40 no qualified Example 7 158 1.25 no qualified Example 8 165 1.30 no qualified Example 9 172 1.42 no qualified Example 10 175 1.46 no qualified Embodiment 11 174 1.44 no qualified
[0124] Result analysis: The difference between Example 7-11 and Example 5 is that when preparing green and healthy phase change energy storage materials, the total weight of liquid paraffin and titanate coupling agent modified copper nanoparticles accounts for different proportions in the green and healthy phase change energy storage materials. Combined with the experimental test results in Table 5, it can be seen that when the total weight of liquid paraffin and titanate coupling agent modified copper nanoparticles accounts for 55-61% in the green and healthy phase change energy storage materials, the comprehensive performance of the green and healthy phase change energy storage materials is better. When the total weight of liquid paraffin and titanate coupling agent modified copper nanoparticles accounts for 58% in the green and healthy phase change energy storage materials, the comprehensive performance of the green and healthy phase change energy storage materials is the best. When the proportion is too high or too low, the comprehensive performance is reduced.
[0125] Example 12
[0126] The difference between this example and Example 10 is that in this example, an equal amount of polyvinyl pyrrolidone is used instead of calcium lignin sulfonate.
[0127] Embodiment 13
[0128] The difference between this embodiment and embodiment 10 is that in this embodiment, calcium lignin sulfonate and polyvinyl pyrrolidone with a mass ratio of 1:1 replace calcium lignin sulfonate.
[0129] Table 6 - Experimental test results of Examples 12-15
[0130] serial number Latent heat (J / g) Thermal conductivity (W / mK) Is it leaked? Flame retardant Example 10 175 1.46 no qualified Example 12 176 1.48 no qualified Embodiment 13 179 1.52 no qualified
[0131] Result analysis: The difference between Examples 12-13 and Example 10 is that different preparation parameters of the titanate coupling agent-modified copper nanoparticles are used in preparing the green and healthy phase-change energy storage material. Combined with the experimental test results in Table 6, it can be seen that the green and healthy phase-change energy storage material prepared by Example 13 has better comprehensive performance.
[0132] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.
Claims
1. A green and healthy phase change energy storage material, characterized in that: In parts by weight, the phase change energy storage material is halloysite nanotube microcapsules; the halloysite nanotube microcapsules include the following raw materials in parts by weight: 10-30 parts of halloysite nanotubes, 0.5-3 parts of 3-aminopropyltriethoxysilane, 50-90 parts of liquid paraffin, 5-9 parts of titanate coupling agent modified copper nanoparticles, 5-20 parts of nano aluminum hydroxide, 2.5-10 parts of nano borate, and 5-15 parts of a compatibilizer; The halloysite nanotube microcapsules further include sodium dodecyl sulfate, methyl methacrylate and an initiator; The amount of sodium dodecyl sulfate added is 1%-5% of the weight of the halloysite nanotubes; The amount of methyl methacrylate added is 5%-15% by weight of the halloysite nanotubes; The added amount of the initiator is 0.5%-1.5% of the weight of methyl methacrylate.
2. The green and healthy phase change energy storage material according to claim 1, characterized in that: The weight ratio of the liquid paraffin and the titanate coupling agent modified copper nanoparticles is 1:(0.08-0.15).
3. The green and healthy phase change energy storage material according to claim 2 is characterized in that: The weight ratio of the liquid paraffin and the titanate coupling agent modified copper nanoparticles is 1:0.
1.
4. The green and healthy phase change energy storage material according to claim 1, characterized in that: The diameter of the halloysite nanotube is 30-60 nm and the length is 0.8-1.5 μm.
5. The green and healthy phase change energy storage material according to claim 1, characterized in that: The compatibilizer includes at least one of calcium lignin sulfonate and polyvinyl pyrrolidone.
6. The green and healthy phase change energy storage material according to claim 5, characterized in that: The compatibilizer includes calcium lignin sulfonate and polyvinyl pyrrolidone in a weight ratio of 1:
1.
7. The green and healthy phase change energy storage material according to claim 1, characterized in that: The initiator includes azobisisobutyronitrile.
8. A method for producing the green and healthy phase change energy storage material according to any one of claims 1 to 7, characterized in that: The production method comprises the following steps: S1, calcining the halloysite nanotubes and then adding them to a hydrochloric acid solution, stirring and reacting at 60-80° C. for 2-4 hours, separating and washing to obtain acid-treated halloysite nanotubes; S2, mixing the acid-treated halloysite nanotubes, ethanol and 3-aminopropyltriethoxysilane in step S1, stirring and reacting at 60-80° C. for 4-6 hours, separating and washing to obtain 3-aminopropyltriethoxysilane-modified halloysite nanotubes; S3, mixing liquid paraffin and titanate coupling agent modified copper nanoparticles to prepare a phase change material, which is set aside; mixing a compatibilizer with water to prepare a compatibilizer aqueous solution, which is set aside; S4, mixing the 3-aminopropyltriethoxysilane-modified halloysite nanotubes described in step S2, the phase change material described in step S3, the compatibilizer aqueous solution described in step S3, and the nano-aluminum hydroxide and nano-borate with water to prepare an aqueous phase; S5. Add sodium dodecyl sulfate to the aqueous phase in step S4 and stir to obtain an emulsion, and add methyl methacrylate and an initiator to the emulsion. Under nitrogen protection, react at 60-80° C. for 2-5 hours, and obtain the halloysite nanotube microcapsules after centrifugation, washing and drying.
9. The method for producing the green and healthy phase change energy storage material according to claim 8, characterized in that: The particle size of the halloysite nanotube microcapsule is 1-10 μm.
10. Application of the green and healthy phase change energy storage material according to any one of claims 1 to 7 in the fields of building insulation materials, cold chain transportation packaging, and heat dissipation of electronic equipment.
Citation Information
Patent Citations
Heat-storage constant-temperature nanometer composite phase-change material, and preparation method thereof
CN109705813A
Flexible high-thermal-conductivity composite phase change film and preparation method thereof
CN114181670A
Drug-loaded halloysite nanotube and preparation method thereof
CN115501167A
High-thermal-conductivity shaped phase change material and preparation method thereof
CN115637136A
Phase change composite material coated diaphragm and preparation method thereof
CN117117428A